Contribution of Restaurant, Hotel, and Advertising Taxes to Local Revenue (PAD) in Manokwari During Economic Volatility (2019–2023) - Sumari, Jenita; Wuriasih, Anik (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the effectiveness and contribution of restaurant, hotel, and advertising taxes to the Local Own-Source Revenue (PAD) of Manokwari Regency from 2019 to 2023, within the context of inflation dynamics and economic growth. Employing a quantitative approach through descriptive statistics, Pearson correlation, and multiple linear regression analysis, this study examines the simultaneous effects of these variables on PAD. The findings reveal that all three taxes are categorized as highly effective, with restaurant tax achieving an average effectiveness of 108.44%, hotel tax 97.85%, and advertising tax 97.01%. However, only advertising tax demonstrates a significant contribution to PAD, showing a very strong correlation (r = 0.977; p < 0.01). Although restaurant and hotel taxes are collected effectively, their contribution remains relatively low and statistically insignificant. Inflation and economic growth variables display positive but statistically insignificant correlations. These results highlight the paradox between tax effectiveness and its actual contribution, emphasizing the need for context-specific and data-driven fiscal policy approaches. This study contributes to the development of a regional fiscal model that is responsive to local economic dynamics and supports the sustainable optimization of local revenue sources.